Faculty and Staff Perceptions of Title IX Mandatory Reporting Policies at Two Institutions - Koon-Magnin, Sarah (Violence against women, 2023)
Most faculty and staff at postsecondary institutions are mandatory reporters who must disclose sexual assault to a Title IX Coordinator. However, scholarship examining their role is sparse. We address this gap by investigating perceptions and experiences of employees (n = 166) at two institutions. Findings indicate that most employees are aware of their reporting duties, likely to comply, have received training, and support mandated reporting. Additionally, we find significant sociodemographic differences in perceptions of mandatory reporting. Those who have had a direct experience reporting have mixed reactions to the process. We discuss research and policy implications.